2007
DOI: 10.1007/s00432-006-0182-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemoimmunotherapy for cutaneous melanoma with dacarbazine and epifocal contact sensitizers: results of a nationwide survey of the German Dermatologic Co-operative Oncology Group

Abstract: Epifocal DNCB combined with DTIC is effective in patients with regionally metastasized melanoma not amenable to surgery or isolated limb perfusion, whereas in stage IV disease in spite of few durable remissions the addition of DNCB does not improve the therapeutic efficacy of DTIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 26 publications
1
19
0
2
Order By: Relevance
“…We therefore propose that stimulation of TLR, IL-1R, IL-18R, and IL-12R may all favor the development of CHS to DNTB or other Ags, as reported for IL-12 (14). Consequently, NLR activation may be an interesting target as an adjuvant for vaccines and tumor vaccination, and it should be noted here that DNCB has been used to promote inflammation and favor immunerejection in metastatic melanoma patients (31).…”
Section: Discussionmentioning
confidence: 99%
“…We therefore propose that stimulation of TLR, IL-1R, IL-18R, and IL-12R may all favor the development of CHS to DNTB or other Ags, as reported for IL-12 (14). Consequently, NLR activation may be an interesting target as an adjuvant for vaccines and tumor vaccination, and it should be noted here that DNCB has been used to promote inflammation and favor immunerejection in metastatic melanoma patients (31).…”
Section: Discussionmentioning
confidence: 99%
“…This led to local therapeutic response rates in 37 % of patients. In a retrospective analysis of 72 patients treated with a combination of DNCB and DTIC IV, Terheyden et al [427] found response rates of 62 % in patients with stage III disease, yet only of 9 % in patients with stage IV disease. The latter finding was not superior to DTIC alone.…”
Section: Immunotherapymentioning
confidence: 99%
“…Terheyden et al (34) used dinitrochlorobenzene to induce contact dermatitis, which in combination with DTIC therapy, was used to treat metastatic MM. The objective response rate was 62% in patients with stage III MM (n=39) and 9% in those with stage IV MM (n=33), and >50% of patients remained progression-free for 1 year regardless of the stage of MM (35).…”
Section: Discussionmentioning
confidence: 99%